2018
DOI: 10.1002/2017gl076664
|View full text |Cite
|
Sign up to set email alerts
|

A New Estimate of North American Mountain Snow Accumulation From Regional Climate Model Simulations

Abstract: Despite the importance of mountain snowpack to understanding the water and energy cycles in North America's montane regions, no reliable mountain snow climatology exists for the entire continent. We present a new estimate of mountain snow water equivalent (SWE) for North America from regional climate model simulations. Climatological peak SWE in North America mountains is 1,006 km3, 2.94 times larger than previous estimates from reanalyses. By combining this mountain SWE value with the best available global pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 61 publications
4
71
0
Order By: Relevance
“…While the classification scheme proposed by Harpold et al () is straightforward and easy to use, it does not account for the co‐occurrence of warm and dry conditions, which have been shown to result in significantly more severe summer low flow periods than only dry conditions alone (Dierauer et al, ). Additionally, it does not account for spatial and temporal variations in the timing of peak SWE, which varies substantially between and within mountain ranges (Wrzesien et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…While the classification scheme proposed by Harpold et al () is straightforward and easy to use, it does not account for the co‐occurrence of warm and dry conditions, which have been shown to result in significantly more severe summer low flow periods than only dry conditions alone (Dierauer et al, ). Additionally, it does not account for spatial and temporal variations in the timing of peak SWE, which varies substantially between and within mountain ranges (Wrzesien et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas Wrzesien et al () identified a bias in current estimates of SWS over mountain ranges, the primary goal in this paper is to assess whether the role of precipitation is correctly estimated during the cool season (October through March) across entire watersheds. To achieve this objective, we compare representative‐year wintertime precipitation and SWS estimates from existing global data sets to the WRF simulations performed by Wrzesien et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Wrzesien et al () identified a bias in current estimates of SWS over mountain ranges, the primary goal in this paper is to assess whether the role of precipitation is correctly estimated during the cool season (October through March) across entire watersheds. To achieve this objective, we compare representative‐year wintertime precipitation and SWS estimates from existing global data sets to the WRF simulations performed by Wrzesien et al (). Past studies cited above suggest that WRF produces reasonable results in mountain environments; though model evaluation against gridded SWE (Qian et al, ; Wrzesien et al, ), precipitation (Hughes et al, ), or even terrestrial water storage estimates from the Gravity Recovery and Climate Experiment satellite (Frappart et al, ; Wrzesien et al, ) is possible, no true validation data set exists.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations